2002
DOI: 10.1097/00001888-200209000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Using a Productivity-based Physician Compensation Program at an Academic Health Center

Abstract: Successful productivity-based physician compensation programs can be developed for AHCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 5 publications
0
35
0
Order By: Relevance
“…Defining clinical activity benchmarks was straightforward using work relative value unit (wRVU) data for academic hematologists and academic medical oncologists from sources such as the Medical Group Management Association 6 or Faculty Practice Solutions Center. 7 The source of data used must be carefully considered because sources are not always the same.…”
Section: Mission Focusedmentioning
confidence: 99%
See 1 more Smart Citation
“…Defining clinical activity benchmarks was straightforward using work relative value unit (wRVU) data for academic hematologists and academic medical oncologists from sources such as the Medical Group Management Association 6 or Faculty Practice Solutions Center. 7 The source of data used must be carefully considered because sources are not always the same.…”
Section: Mission Focusedmentioning
confidence: 99%
“…Each of the salary scales had incremental increases for rank (assistant, associate, or full professor) as well as steps at each rank roughly proportional to the number of years at a particular rank. Thus, as opposed to some mission-based models that exclude consideration of academic rank in defining reimbursement, 6 our model rewards academic advancement, as is the case for other members of the university academic community.…”
Section: Productivity-based Funds Flowmentioning
confidence: 99%
“…Reduced compensation levels since the advent of managed care and reductions in Medicare funding related to the Balanced Budget Act of 1997 have forced all AMCs to operate in a more fiscally competitive environment (5)(6)(7)(8)(9). This has led to the development of different models to link salary to productivity (10 -13).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these shortcomings, there is still a lot to be accomplished as we stand on the cutting edge of miraculous medical breakthroughs. Andreae and Freed 19 reviewed physician compensation in pediatrics and the University of Michigan and suggested that compensation packages can be developed on the basis of an individual's contribution to clinical care, teaching, and research, with excess productivity being rewarded. Surgeons are natural optimists, which means that there is always a tunnel and a light, although they may not always be in focus at the same time.…”
Section: Mentoring Academic Surgeonsmentioning
confidence: 99%